Analisis Eksploratif Channel YouTube Badan Wakaf Indonesia - Haq, Furqonul (Brida Provinsi Jambi, 2024)
YouTube is one of the most popular information and entertainment media today. The information and entertainment provided by YouTube is in the form of videos. YouTube channels can be subscribed for free and paid. YouTube is a company founded by three former PayPal employees in 2005. Then in 2006 YouTube was bought by Google. The most YouTube user accounts in the world and one of the most user countries is Indonesia. Information related to the activities and performance of an institution can be obtained from its YouTube channel. To find out the activities and performance of the Indonesian Waqf Board (BWI) institution can be seen on its YouTube channel called Badan Wakaf Indonesia TV. The purpose of the research on this YouTube channel is to analyze the profile and columns on the BWI YouTube channel. The research method used is descriptive qualitative with explorative analysis. The results showed that BWI's YouTube channel has a profile with 3.01 thousand subscribers and 312 videos. Posts on BWI's YouTube channel only consist of video posts (no image posts). BWI's YouTube channel has nine columns. Of the nine columns (home, videos, shorts, live, playlist, community, channels, about, and search), only seven columns can be analyzed exploratively. Meanwhile, the community and channels columns cannot be analyzed exploratively.